Effect of mouth wash extracted from Salvadora persica (Miswak) on dental plaque formation: A clinical trail - Al-Bayaty, F.H.; Al-Koubaisi, A.H.; Ali, N.A.W.; Abdulla, M.A. (Academic Journals, 2010)
Chewing sticks or Miswak are used for teeth cleaning in many parts of the world, these Miswaks are believed to contain chemical substances which inhibit plaque formation and gingivitis. In the present study, Salvadora persica (Miswak) was extracted with 60% ethanol and was examined for its toxic effect, assessed its antibacterial activity and evaluated clinically for its effect on dental plaque formation. A 4 day plaque regrowth, double - blind, crossover design was used in which 10 dental students volunteers were rendered plaque free (0.3), ceased tooth cleaning, then, asked to rinse twice daily for 1.5 min each time with 10 ml of chlorhexidine 0.2% mouth rinse and three times daily for 1.5 min each time with 10 ml of S. persica 10% solution and placebo mouth rinse. On day five, plaque was scored by the plaque index system (PLI). A wash out period of 2 days was allowed in which the volunteers returned to self- performed plaque control, then a new test period was initiated. Statistical analysis showed that the mean PLI score were 1.48 for S. persica mouth rinse, 0.48 for chlorhexidine and 2.07 for placebo mouth rinse. Acute toxicity test revealed no mortality among the experimental animals which is an indication that S. persica crude extract solution is well tolerated, disk diffusion test showed a marked antibacterial effect in vitro and this effect is concentration dependent, had an effect in in vivo, but this effect cannot be considered absolute.